Training Intensity Distribution, Training Volume, and Periodization Models in Elite Swimmers: A Systematic Review - González Ravé, José María; Hermosilla, Francisco; González Mohíno, Fernando; Casado, Arturo; Pyne, David B. (My University, 2021)
A well-planned periodized approach allows swimmers to achieve peak performance at the major national and international competitions. Purpose: To identify the main characteristics of endurance training for highly trained swimmers described by the training intensity distribution (TID), volume, and periodization models. Methods: The electronic databases Scopus, PubMed, and Web of Science were searched using a comprehensive list of relevant terms. Studies that investigated the effect of the periodization of training in swimming, with the training load (volume, TID) and periodization reported, were included in the systematic review. Results: A total of 3487 studies were identified, and after removal of duplicates and elimination of papers based on title and abstract screening, 17 articles remained. A further 8 articles were excluded after full text review, leaving a final total of 9 studies in the systematic review. The evidence levels were 1b for intervention studies (n = 3) and 2b for (observational) retrospective studies (n = 6). The sprint swimmers typically followed a polarized and threshold TID, the middle-distance swimmers followed a threshold and pyramidal TID, and the long-distance swimmers primarily followed a pyramidal TID. The periodization model identified in the majority of studies selected is characterized by wave-like cycles in units like mesocycles to promote physiological adaptations and skill acquisition. Conclusions: Highly trained swimmers follow a training volume and TID based on their primary event. There is a need for further experimental studies on the effects of block and reverse periodization models on swimming performance. Although observational studies of training have limited evidence, it is unclear whether a different training/periodization approach would yield better results. Keywords: competition; endurance; physiological adaptations; swimming; training load.